Cyber Security: Power and Technology (Intelligent Systems, Control and Automation: Science and Engineering,, 2018)
This book gathers the latest research results of scientists from different countries who have made essential contributions to the novel analysis of cyber security. Addressing open problems in the cyber world, the book consists of two parts. Part I focuses on cyber operations as a new tool in global security policy, while Part II focuses on new cyber security technologies when building cyber power capabilities. The topics discussed include strategic perspectives on cyber security and cyber warfare, cyber security implementation, strategic communication, trusted computing, password cracking, systems security and network security among others.